Implementation of a food science and nutrition module in a dental undergraduate curriculum. (27th May 2022) - Crowe, Michael; O'Sullivan, Michael; Winning, Lewis; Cassetti, Oscar; O'Connell, Brian; O'Sullivan, Aifric; Gibney, Eileen; Doyle, Suzanne L.; Bennett, Annemarie; Moynihan, Paula
Abstract: Introduction: To outline the development and implementation of a food science and nutrition module for dental undergraduate students that provides basic knowledge and clinical skills for improving oral health outcomes and understanding their importance for overall health. Materials and methods: Interdisciplinary discussions with professionals with expertise in food science and nutrition, including dentists, dietitians and nutritionists, were held to agree on core subject areas in line with the evidence base. The module was delivered online to 2nd‐year dental students due to COVID‐19 restrictions. Students completed an online evaluation on completing the module. Final examination consisted of one essay question. Results: Subject areas and learning outcomes were derived from current and previous approaches to curriculum development. A total of 14 prerecorded lectures, including healthy eating guidelines, dietary assessment, specific oral effects of diet and food constituents were delivered and tutorials provided. The evaluation survey had a 90% ( n  = 39/43) response rate. A majority indicated that the course was "interesting, " "worth doing " (59%) and "provided a good evidence base to understand nutrition and oral health" (87%). Nearly all students (92%) agreed that the course was "sufficiently structured to allow understanding of the key topics " and that "a good understanding of nutrition is important for a dentist" (95%). Conclusion: A food science and nutrition module developed by a multidisciplinary team enabled dental students to gain an understanding of the role of diet in oral and overall health. The module facilitated the development of skills that enable students to utilise dietary assessment techniques and promote dietary interventions beneficial to oral health. The approach taken may act as a template for other institutions.